Differential Taxation, Public Goods, and Economic Efficiency - Stiglitz, J. E.; Dasgupta, P. (Review of Economic Studies, 1971)
J. E. Stiglitz, P. Dasgupta; Differential Taxation, Public Goods, and Economic Efficiency12, The Review of Economic Studies, Volume 38, Issue 2, 1 April 1971, P